Last Act of Napoleon’s Russian Campaign: On the Monograph of V. N. Zemtsov. Review of: Zemtsov, V. N. (2024). Russkaia kampaniia Napoleona: poslednii akt (dekabr’ 1812 g. — ianvar’ 1813 g.) [Napoleon’s Russian Campaign: The Last Act (December 1812 — January 1813)]. Moscow: Politicheskaia entsiklopediia - Postnikova, Alena А. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2025)
This essay makes an attempt to assess the place of the latest research by the Russian historian V. N. Zemtsov in the modern historiography of the problems of the Napoleonic era. The author comes to the conclusion that the combination of methods of military-historical anthropology with an extensive database of sources, including manuscript documents from the archives of France and Austria, not counting the published materials, certainly makes this study a very relevant, noticeable and vivid phenomenon of the world historiography of this topic.